Rape Cases in Islamic Boarding Schools: How are Victims Protected and Law Enforced? - Suci, Tiram Sheenaranti; Al Ghani, Muhammad Firman (Indonesia Media Law Review, 2023)
Indonesia is a state of law where the law is present aims to create a safe, orderly, and and prosperous atmosphere in the life of society and the state. However, on the other hand, there is still a widespread occurrence of moral crimes that cause a lot of suffering for their victims. One of the crime cases that received a lot of attention is the rape case that occurred in the Tahfidz Madani Bandung Boarding School, in the case the perpetrator committed the crime of rape against 12 santriwati until some of the victims experienced pregnancy. This study uses juridical-normative method with an approach to the case (case approach), this study aims to determine the rights of victims of rape in criminal law and analyze the form of legal protection for victims of rape that occurred in the Islamic boarding school Tahfidz Madani Bandung. This study will discuss related cases that occur through the perspective of victimology. The results of the discussion obtained by this study are: (1). through the perspective of victimology used, this study results that the existence of certain factors that encourage the occurrence of crime against the victim, but it is also found the existence of psychic suffering experienced by the victim as a result of the crime he experienced; (2). The decision that has been handed down by the Bandung high court against this case is to improve the decision of the Bandung state court and provide some protection to the victim for the actions of the perpetrator. The conclusion of this study is women as victims of rape, especially if the victim of rape is a minor will experience a variety of severe suffering. Bandung High Court Decision Number 86 / Pid.Sus / 2022 / PT.BDG in addition to imposing the death penalty against the perpetrator also imposes restitution to the perpetrator confiscating all assets belonging to the defendant